2019
DOI: 10.1152/ajprenal.00373.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oxalate and kidney stone formation

Abstract: Dietary oxalate is plant-derived and may be a component of vegetables, nuts, fruits, and grains. In normal individuals, approximately half of urinary oxalate is derived from the diet and half from endogenous synthesis. The amount of oxalate excreted in urine plays an important role in calcium oxalate stone formation. Large epidemiological cohort studies have demonstrated that urinary oxalate excretion is a continuous variable when indexed to stone risk. Thus, individuals with oxalate excretions >25 mg/day m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 55 publications
0
89
0
Order By: Relevance
“…The KSD-NTN group also had a higher level of Firmicutes and a higher level of the associated genus Lactobacillus. Lactobacillus can decrease the excretion of urinary oxalate [34], which is responsible for the formation of KSD [35]. Thus, the increase in probiotic bacteria such as Lactobacillus accompanying the increase in pathogenic bacteria in the KSD-NTN group (compared to the HC group) might be a self-protective response in the urinary microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…The KSD-NTN group also had a higher level of Firmicutes and a higher level of the associated genus Lactobacillus. Lactobacillus can decrease the excretion of urinary oxalate [34], which is responsible for the formation of KSD [35]. Thus, the increase in probiotic bacteria such as Lactobacillus accompanying the increase in pathogenic bacteria in the KSD-NTN group (compared to the HC group) might be a self-protective response in the urinary microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Chan School of Public Health Nutrition Department and this may be a valid asset either for determining patients with a very high oxalate intake and for reducing dietary oxalate intake in subjects at risk [84]. The non-linear association between dietary and urinary oxalate content was recently shown by Mitchell et al There is a 2.7 mg increase in urinary oxalate excretion for every 100 mg of oxalate consumption, within a range of 50-750 mg/day and on a 1000 mg/day calcium diet [79]. However, even when dietary oxalate intake is lower than 50 mg/day, it significantly contributes to urinary oxalate excretion.…”
Section: Dietary Oxalate and Kidney Outcomesmentioning
confidence: 93%
“…Dietary oxalate intake is one of the modifiable risk factors of hyperoxaluria [79]. Although not without limitations, 24 h urine collection is the most common method for estimating daily oxalate consumption and absorption [1].…”
Section: Dietary Oxalate and Kidney Outcomesmentioning
confidence: 99%
“…The second important and unanswered finding derived from the current study is that urine oxalate significantly increased after statin use. Previous literature suggested that >50% of urine oxalate comes from endogenous hepatic production and the reminder variably comes from the diet 29 . One of the most common adverse effects of statin is hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%